The Modernization Potential of Gas Turbines in the Coal-Fired Power Industry Thermal and Economic Effectiveness - Bartnik, Ryszard; SpringerLink (Online service) (London : Springer London : Imprint: Springer, 2013)
The opportunity of repowering the existing condensing power stations by means of  gas turbogenerators offers an important opportunity to considerably improvement of their energy efficiency. The Modernization Potential of Gas turbines in the Coal-Fired Power Industry presents the methodology, calculation procedures and tools used to support enterprise planning for adapting power stations to dual-fuel gas-steam combined-cycle technologies. Both the conceptual and practical aspects of the conversion of existing coal-fired power plants is covered. Discussions of the feasibility, advantages and disadvantages and possible methods are supported by chapters presenting equations of energy efficiency for the conditions of repowering a power unit by installing a gas turbogenerator in a parallel system and the results of technical calculations involving the selection heating structures of heat recovery steam generators. A methodology for analyzing thermodynamic and economic effectiveness for the selection of a structure of the heat recovery steam generator for the repowered power unit is also explained. The Modernization Potential of Gas turbines in the Coal-Fired Power Industry is an informative monograph written for researchers, postgraduate students and policy makers in power engineering.
1.Introduction -- 2.Thermodynamic fundamentals for production of electric power in hierarchical j-cycle systems -- 3.In-series or parallel system? -- 4.Energy efficiency of repowering a power unit by installing a gas turbogenerator in a parallel system -- 5.Selection of an optimum gas turbogenerator for the repowered power unit -- 6.Selection of the structure of the heat recovery steam generator for the repowered power unit -- 7.Comparison of specific cost of producing electricity in a 370 MW power unit adapted to dual-fuel gas-steam system and in a new one operating under supercritical parameters -- 8.Summary and final conclusions.
Keywords: Renewable energy resources; Energy efficiency; Thermodynamics; Heat engineering; Heat transfer; Mass transfer; Renewable and Green Energy; Energy Efficiency; Engineering Thermodynamics, Heat and Mass Transfer